PENGARUH BUDAYA KERJA DAN EMOTION INTELLEGENCE TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA SATUAN POLISI PAMONG PRAJA KOTA PAYAKUMBUH - Fiana, Aswil; Heliyani, Heliyani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to examine and analyze the influence of Work Culture and Emotional Intelligence on Employee Performance with Job Satisfaction as an Intervening Variable at the Civil Service Police Unit (Satpol PP) of Payakumbuh City. This research is classified as Explanatory Research using a Quantitative approach. The sample consists of all Civil Servants (PNS) working at the Civil Service Police Unit of Payakumbuh City, totaling 40 individuals. The sampling technique used is saturated sampling, where the entire population is used as the research sample. The data used in this study is primary data collected through questionnaires distributed to respondents. The data was processed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the SmartPLS 3 application. The hypothesis testing results show that Work Culture has an insignificant effect on employee performance, while Emotional Intelligence has a significant effect on performance. Job Satisfaction has a positive and significant effect on employee performance. Furthermore, Emotional Intelligence positively and significantly affects job satisfaction. The indirect effect of Work Culture on performance through job satisfaction is found to be insignificant, whereas Job Satisfaction significantly mediates the effect of Emotional Intelligence on employee performance at the Civil Service Police Unit of Payakumbuh City.Keywords: Work Culture, Emotional Intelligence, Job Satisfaction, Performance